Marketing the Miracles: Studies on the Commodification of the Quran, Prayer, and Sadaqa - Darmawan, Dadang (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2023)
Religion is a miracle. The history of religion is filled with stories of the miracles of its founder and leaders. Religion does not intend to sell miracles for worldly gain because the purpose of religion is spiritual. Nevertheless, in reality, the miracles offered by religion are often commodified. This study examines the commodification of religion in Indonesia, especially those related to the Quran, sadaqa, and glory. This research uses qualitative methods with Habermas’s hermeneutical approach to uncover the economic motives behind the utterances delivered by certain religious figures. The results showed that certain religious figures had commodified the Quran (as a material element), prayer (as a suprarational element), and sadaqa (as a social element) through the utterances they delivered. This research found that religion, based on ordinary people’s point of view, is nothing more than a solution to their complex problems. These social conditions have given religious elites the opportunity to commodify religion. In addition, the research proposes a theoretical contribution that “the perfect religious commodification” should consist of and offer three elements: material, suprarational, and social benefits. This combination of benefits may be the key to the effectiveness of religious commodification and the continued support of ordinary people.